ABT-263 Reduces Hypertrophic Scars by Targeting Apoptosis of Myofibroblasts - Yang, Xiaolan; Xiao, Yongqiang; Zhong, Chenjian; Shu, Futing; Xiao, Shichu; Zheng, Yongjun; Xia, Zhaofan (Frontiers in Pharmacology, 2021)
Background: Inhibiting proliferation and inducing apoptosis of myofibroblasts is becoming one of the promising and effective ways to treat hypertrophic scar. ABT-263, as an orally bioavailable BCL-2 family inhibitor, has showed great anti-tumor characteristics by targeting tumor cells apoptosis. The objective of this study was to explore whether ABT-263 could target apoptosis of over-activated myofibroblasts in hypertrophic scar. Methods: In vivo, we used ABT-263 to treat scars in a rabbit ear scar model. Photographs and ultrasound examination were taken weekly, and scars were harvested on day 42 for further Masson trichrome staining. In vitro, the expression levels of BCL-2 family members, including pro-survival proteins, activators and effectors, were detected systematically in hypertrophic scar tissues and adjacent normal skin tissues, as well as in human hypertrophic scar fibroblasts (HSFs) and human normal dermal fibroblasts (HFBs). The roles of ABT-263 in apoptosis and proliferation of HSFs and HFBs were determined by Annexin V/PI assay, CCK-8 kit and cell cycle analysis. Mitochondrial membrane potential was evaluated by JC-1 staining and the expression of type I/III collagen and α-SMA were measured by PCR, western blotting and immunofluorescence staining. Furthermore, immunoprecipitation was performed to explore the potential mechanism. Results: In vivo, ABT-263 could significantly improve the scar appearance and collagen arrangement, decrease scar elevation index (SEI), and induce cell apoptosis. In vitro, the expression levels of BCL-2, BCL-XL and BIM were significantly higher in scar tissues and HSFs than that in normal skin tissues and HFBs. ABT-263 selectively induced HSFs apoptosis by releasing BIM from binding with pro-survival proteins. Moreover, ABT-263 inhibited HSFs proliferation and reduced the expression of α-SMA and type I/III collagen in a concentration- and time- dependent manner. Conclusions: HSFs showed increased mitochondrial priming with higher level of pro-apoptotic activator BIM and were primed to death. ABT-263 showed great therapeutic ability in the treatment of hypertrophic scar by targeting HSFs.